Does MR Sialography Have A Greater Diagnostic Accuracy Than Conventional X-Ray And Digital Subtraction Sialography In Detecting Salivary Glands Disease? A Literature Review - Uddin, SM (Nepalese Journal of Radiology, 2012)
Aim: The main aim was to determine the diagnostic accuracy of MR Sialography as compared to conventional x-ray and digital sialography in detecting salivary gland diseases on the basis of research evidences available in the literature. Description: It is noticed that almost all people develop illness of salivary glands at some stage of their lives. The major effects on salivary glands become evident as stones; infection tumors which may also involve related organs. Imaging methods like Ultrasound, Computed Tomography (CT) and Digital subtraction sialography (DSS) are used for assessment of parotid, sub-mandibular and sub-lingual glands in addition to conventional x-ray sialography which is marked as a gold standard for salivary glands assessment. Due to the non-invasive nature and level of comfort, MR Sialography is now being considered as an advanced technique for the detection of stones and tumor spread in the soft tissues with no risk of radiation exposure. Methods and Results: Different databases which include Science direct, CINAHL, Ebesco Host, PubMed, Swetswise, Wiley Interscience, sage pub, and The Cochrane library were explored to get published literature. Total 10 studies were included and critically appraised under critical appraisal skills programme (CASP) tool. Conclusion: The review proposed that though the use of MRS as the only diagnostic examination is useful but X-ray sialography remains the standard investigation tool due to its higher spatial resolution. MRS can be utilized as an alternative imaging technique by using special MR sequences such as 3D CISS and RARE where x-ray sialography cannot be performed. DOI: http://dx.doi.org/10.3126/njr.v1i1.6329 Nepalese Journal of Radiology Vol.1(1): 70-77